The skilled helper : a problem-management and opportunity-development approach to helping - Egan, Gerard (Belmont, Calif. : Brooks/Cole, Cengage Learning, 2014)
Internationally recognised for its successful problem-management approach to effective helping, this book offers a step-by-step guide to the counselling process.
Illustration on p. 2 of cover.
First published under the title: The skilled helper: a model for systematic helping and interpersonal relating, c1975.
Includes bibliographical references (p. 405-449) and indexes.
Keywords: Counseling psychology; Helping behavior